ANALISIS IMPLEMENTASI KEBIJAKAN VAKSINASI COVID-19 DI PROVINSI SULAWESI SELATAN - Fitria, Ika; Cahyani, Afrilia; Yasmin, Muhammad; Jufri, Supriadi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
Indonesia is implementing a Covid-19 vaccination policy as part of the government's efforts reduce the spread of the covid-19 virus which started in 2019. Goal this research is to determine the implementation of the Covid-19 vaccination policy in the Province South Sulawesi. This research uses a qualitative descriptive research design with data collection techniques obtained through observation, interviews and activities documentation. This research data analysis technique is interactive starting from reduction data, presenting data and drawing conclusions using triangulation data as a technique for checking the validity of findings. The results of this research show that the implementation of the Covid-19 vaccination policy in South Sulawesi Province, with Using Edward III's theory of policy implementation shows that communication in terms of consistency has not been effective, resources in terms of resources equipment and budget are not yet optimal. Meanwhile, bureaucratic structure and disposition it's been going well.